2022
DOI: 10.1093/nar/gkac912
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory landscape of multiple brain regions in outbred heterogeneous stock rats

Abstract: Heterogeneous Stock (HS) rats are a genetically diverse outbred rat population that is widely used for studying genetics of behavioral and physiological traits. Mapping Quantitative Trait Loci (QTL) associated with transcriptional changes would help to identify mechanisms underlying these traits. We generated genotype and transcriptome data for five brain regions from 88 HS rats. We identified 21 392 cis-QTLs associated with expression and splicing changes across all five brain regions and validated their effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 70 publications
6
47
1
Order By: Relevance
“…We examined the impact of the upgraded reference assembly on the yield and relative numbers of expression quantitative trait locus (eQTL) using a large RNA-seq dataset for nucleus accumbens. 29 We identified associations that would be labeled as trans-eQTLs using one reference but cis-eQTL using the other, due to relocation of the SNP and/or the TSS. The expectation is that assembly errors will give rise to spurious trans-eQTLs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the impact of the upgraded reference assembly on the yield and relative numbers of expression quantitative trait locus (eQTL) using a large RNA-seq dataset for nucleus accumbens. 29 We identified associations that would be labeled as trans-eQTLs using one reference but cis-eQTL using the other, due to relocation of the SNP and/or the TSS. The expectation is that assembly errors will give rise to spurious trans-eQTLs.…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq data was downloaded from RatGTEx. 29 Brains were extracted from 88 HS rats. Rats were housed under standard laboratory conditions.…”
Section: Methodsmentioning
confidence: 99%
“…CiTruss revealed that the pleiotropic effects of eQTLs, a hierarchy in tissue-specific gene regulation, and local and long-range linkage disequilibrium among eQTLs are structured around local and global subnetworks, and disentangled pleiotropic effects into cis -acting and trans -acting eQTLs for local subnetworks and trans -acting and undetermined eQTLs for global subnetworks. One future direction would be to determine a high-resolution map of hierarchical organization of the global subnetworks across tissue types, by applying CiTruss to eQTL data for a wide variety of tissue types from humans 13 , farm animals 16 , and rats 25 . To further investigate the role of local and long-range linkage disequilibrium of eQTLs in gene regulation, we could compare these eQTLs with Hi-C data 26 to see if long-range chromatin interactions overlap with eQTLs in long-range linkage disequilibrium and if topologically associating domains overlap with the regions of linked eQTLs that contain local subnetworks.…”
Section: Discussionmentioning
confidence: 99%
“…RNA expression from three brain regions was measured using high-throughput RNA sequencing on the Illumina HiSeq 4000 platform and a poly-A selection protocol (GSE173141). The original data set [58] included tissue from 88 alcohol and drug naïve heterogeneous stock rats and most rats had RNA-Seq libraries from all the regions. The average…”
Section: Plos Computational Biologymentioning
confidence: 99%